The Effect of Entrepreneurship Education and Family Environment on Entrepreneurial Character - Yanti, Afrina; Indrawati, Henny; Daud, Afrianto (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
Entrepreneurial character is something related to the characteristics of a person's behaviour, character, habits, attitudes and actions in carrying out daily activities both in the academic world, business and dare to take risks to achieve success. This study aims to analyse the effect of entrepreneurship education and family environment on the entrepreneurial character of students in SMPN Pekanbaru City. The population in this study were seventh grade students of SMPN 2 and 18 Pekanbaru City. The sampling technique used is random sampling. The sample size was 189 students, namely 79 respondents from SMPN 2 and 110 respondents from SMPN 18 Pekanbaru City. Data were collected from the results of the questionnaire while the data analysis technique used was descriptive analysis and multiple linear regression analysis. The results showed the influence of entrepreneurship education and family environment simultaneously and partially on the entrepreneurial character of students in social studies economic subjects at SMPN Pekanbaru City. Entrepreneurship education forms a mindset, attitude and behaviour that does not give up easily in the face of challenges, so that to form an entrepreneurial character in students it is necessary to take entrepreneurship education. This condition will be better if the family from the beginning teaches the values of independence, honesty and perseverance. This will make the entrepreneurial character of a child stronger so that later it will be ready to face future challenges.